A Study of the Kidney of the Wistar Rat in Northern Guinea Savannah Zone: The Morphometric Aspect - Onyeanusi, B.I.; Adeniyi, A.A.; Onyeanusi, C.G.; Ayo, J.O.; Ibe, C.S. (Pakistan Journal of Nutrition, 2009)
A morphometric study was carried out on the kidney of the Wistar Rat (WR) using standard laboratory procedures. The mean live weight of the Wistar rat was found to be 140.625±3.078 g. The average kidney weight was 0.605±0.012 g. The right kidney, with a mean weight of 0.632±0.012 g, was significantly (p<0.05) heavier than the left (0.596±0.022 g). The male kidneys were larger than those of the female and the values obtained were 0.633±0.091 g and 0.572±0.132 g, respectively. The relative thickness of the medulla was 5.6. This value (5.6) indicates a high index for the length of the loop of Henle, which acts as a counter current multiplier system and directly increases the ability of the kidney to produce hypertonic urine. This high index thus suggests that the Wistar rat is anatomically adapted within its urinary system (kidney) for water conservation. Furthermore, the present study has provided a baseline morphometric data on the kidney of the Wistar rat in the Northern Savannah zone of Nigeria.